Reactivity of Thiyl Radicals Generated from Thiomethoxide and Dimethyldisulfide in Microheterogeneous Media - Barata Vallejo, Sebastian (2012)
Sodium thiomethoxide and dimethyldisulfide will be shown to beconvenient sources of methyl thiyl radicals for effecting thecis-trans double bond isomerization of oleic acid to elaidic acidresidues arranged in phospholipid bilayers of the microheterogeneousaqueous environment of liposomes. The methods used for methyl thiylradical generation encompass radiolytic and photochemical methods. Theconvenience of these methyl thiyl radical sources will be interpretedin terms of the turn-over numbers in the radical chain cis-transisomerization reaction of unsaturated lipids.